Design and Build WEB-Based Applications as E-Commerce Media for Sales of Custom Products at CLOVE STORE Stores - Nurul Hidayah; Mohammad Suryawinata; Hindarto; Ika Ratna Indra Astutik (Procedia of Engineering and Life Science, 2021)
E-commerce provides information about the items offered by business actors in the form of catalogs, which are given to make it easier for the general public or potential purchasers to select the required product. Making this e-commerce application is for owners who have full control over the e-commerce website or administrators who can enter data on products or services offered, while visitors to e-commerce websites can place orders for those products or services. The results of testing a website-based e-commerce application on the Clove Store store from the trials that have been carried out show that the success rate is 90%, In terms of the benefits of building an e-commerce website, there are many advantages, including for buyers, they don't need to come directly to the store, just by looking at the catalogs available on the website, buyers can directly order available products and for sellers in terms of promotion it will be easier and no need to spend more costs to market their products.